"So many people going the other way" : an examination of the moral strategy of language usage in five novels by Janet Frame : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Pound, Lynette Ruth (Massey University, 1991)
The title quotation is from Janet Frame's novel, Living in the Maniototo (72). Abbreviations and editions of the five primary sources referred to in the text are as follows: EA The Edge of the Alphabets London: W.H. Allen & Co., 1962. SG Scented Gardens for the Blind. London: The Women's Press Ltd., 1982. SS A State of Siege. London: Sirius, 1989. LM Living in the Maniototo. London: The Women's Press Ltd., 1981. CP The Carpathians. London: Century Hutchinson Ltd., 1988. Some of the ideas developed in the chapter on Living in the Maniototo were first sketched out in a paper on that novel (39.498) written in 1990. I wish to thank my supervisor, Dr William Broughton, for his influence and patient guidance in the preparation of this thesis. Sincere thanks also to my husband, Geoff, and our children Mark and Bronwyn for their enthusiastic support.
Keywords: Janet Frame; Criticism and interpretation